Effects of dietary hull-less barley β-glucan on the cholesterol metabolism of hypercholesterolemic hamsters. (15th February 2015) - Tong, Li-Tao; Zhong, Kui; Liu, Liya; Zhou, Xianrong; Qiu, Ju; Zhou, Sumei
Highlights: Hull-less barley β-glucan reduces the concentrations of plasma total cholesterol in hypercholesterolemic hamsters. Hull-less barley β-glucan promotes increases excretions of fecal lipids and bile acids. Hull-less barley β-glucan regulates the activities of HMG-CoA reductase and CYP7A1 in liver. Abstract: The aim of the present study is to investigate the hypocholesterolemic effects of dietary hull-less barley β-glucan (HBG) on cholesterol metabolism in hamsters which were fed a hypercholesterolemic diet. The hamsters were divided into 3 groups and fed experimental diets, containing 5‰ HBG or 5‰ oat β-glucan (OG), for 30 days. The HBG, as well as OG, lowered the concentration of plasma LDL-cholesterol significantly. The excretion of total lipids and cholesterol in feces were increased in HBG and OG groups compared with the control group. The activity of 3-hydroxy-3-methyl glutaryl-coenzyme A (HMG-CoA) reductase in liver was reduced significantly in the HBG group compared with the control and OG groups. The activity of cholesterol 7-α hydroxylase (CYP7A1) in the liver, in the HBG and OG groups, was significantly increased compared with the control group. The concentrations of acetate, propionate and total short chain fatty acids (SCFAs) were not significantly different between the HBG and control groups. These results indicate that dietary HBG reduces the concentration of plasma LDL cholesterol by promoting the excretion of fecal lipids, and regulating the activities of HMG-CoA reductase and CYP7A1 in hypercholesterolemic hamsters.